El meme como herramienta comunicacional del Estado: análisis de la estrategia digital del Reniec en Facebook y su impacto en la interacción ciudadana - Santolalla Huerto, Luis Alberto (2025)
The digital transformation has redefined government communication, shifting from one-way models to strategies that leverage digital languages like humor. This article investigates the use of memes on the RENIEC’s Facebook in 2018 to improve engagement with an audience uninterested in formal language. Using qualitative analysis with Atlas.ti, half a hundred pieces and their interaction levels were examined. The results showed an innovative strategy that generated high interaction, with a mostly positive reception but also criticism regarding the exposure of names and service quality, without generating explicit institutional legitimacy. It is concluded that government communication should consider these resources for its reach, although its impact on long-term trust building is limited and ambivalent.